A Review of Options and Costs for Mitigating GHG Emissions from the U.S. Dairy Sector - Yuhong Lei; Muxi Cheng; Bruce McCarl; Jerry Cessna (Atmosphere, 2024)
The U.S. dairy sector is a significant emitter of methane and nitrous oxide, with the US EPA estimating it produced around 90 Tg CO2 eq. in 2021. This paper reviews the literature on and evaluates various mitigation actions for reducing GHG emissions in the U.S. dairy sector, focusing on both direct and indirect emission sources. We conducted a narrative literature review based on the cradle to gate life-cycle assessment method, covering the entire dairy supply chain up until milk enters retail establishments, including dairy and feed producing farm practices, processing, transportation, and their associated emissions/costs. The papers included were selected over a three year process depending on discussions with experts and issues mentioned in the emerging literature. We review significant opportunities for the U.S. dairy sector to reduce emissions, particularly through improved enteric fermentation and manure management practices. Additionally, we cover the potential for mitigating indirect emissions from feed production, processing, and transportation, areas less frequently covered in existing studies. This review also covers a gap in the literature by integrating economic findings including cost analysis and incentives to mitigate based on the social value of emissions reductions.